Rough Notes to Erasure White Male Privilege, My Senses, and the Story I Cannot Tell - Smith, Dolsy (punctum books, 2020)
We are living through the wrack of the White Male. As the compact between social hierarchy, inherited privilege, and race (reinforced by gender and other normative categories) shows signs of buckling, his rage and resentment threaten us all. For he is a thing possessed: possessed by his own love of possession, and born to a sense that the world belongs to him and him alone. The spoils of oppression lie coiled inside him, a glut he can't digest, and murder beckons behind the respect that he conceives of as his due." A hybrid of critical essay and memoir, and Rough Notes to Erasure contributes to a growing body of work that wrestles with the tacit and embodied nature of privilege and prejudice, and it contributes not only via argument but also through style. Taking inspiration from feminist/queer poetics and what Fred Moten calls "the black avant-garde," these rough notes address the remainder that gets lost in explicit argument, which is the flesh. Where privilege roils through history, and empire whets the appetites. But also where the world catches on its own fractalization by thought, feeling, and desire; and language recovers, for a moment or two, the power to entangle us with our mother tongue.